2020
DOI: 10.1093/cid/ciaa611
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experiences With Staphylococcus aureus and Gram-negative Bacterial Bloodstream Infections: A Qualitative Descriptive Study and Concept Elicitation Phase To Inform Measurement of Patient-reported Quality of Life

Abstract: Background Although Staphylococcus aureus and Gram-negative bacterial bloodstream infections (SAB/GNB) cause substantial morbidity, little is known regarding patient perceptions’ of their impact on quality of life (QOL). Guidance for assessing QOL and disease-specific measures are lacking. We conducted a descriptive qualitative study to gain an in-depth understanding of patients’ experiences with SAB/GNB and concept elicitation phase to inform a patient-reported QOL outcome measure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In addition, a recent study revealed that Staphylococcus aureus bacteremia leads to a significant impact on the quality of life among survivors. 22 Therefore, palliative care consultation may need to be considered more proactively for patients with Staphylococcus aureus bacteremia not only during admission but also in the outpatient setting. Given higher mortality reported in prior studies, the target population would be Staphylococcus aureus bacteremia patients with age >60, MRSA infection, septic shock, endocarditis, underlying cirrhosis or time to positivity of blood cultures less than 12 h. 2 4,23,24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study revealed that Staphylococcus aureus bacteremia leads to a significant impact on the quality of life among survivors. 22 Therefore, palliative care consultation may need to be considered more proactively for patients with Staphylococcus aureus bacteremia not only during admission but also in the outpatient setting. Given higher mortality reported in prior studies, the target population would be Staphylococcus aureus bacteremia patients with age >60, MRSA infection, septic shock, endocarditis, underlying cirrhosis or time to positivity of blood cultures less than 12 h. 2 4,23,24…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study revealed that Staphylococcus aureus bacteremia leads to a significant impact on the quality of life among survivors. 22 Therefore, palliative care consultation may need to be considered more proactively for patients with Staphylococcus aureus bacteremia not only during admission but also in the outpatient setting. Given higher Patients who received palliative care consultation were less likely to undergo an echocardiogram.…”
Section: Discussionmentioning
confidence: 99%
“…Studies benefit from using applied and actionable qualitative data to influence data collection, measurement, and intervention development. [24][25][26][27] The purpose of these cognitive interviews was to ensure adequate coverage in quantitative measures and qualitative interview questions of domains and causes associated with DD in veterans with T2DM. The findings suggest that additional domains and event-based sampling not assessed in the DD Scale are salient to understanding DD among veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Applied qualitative methods, such as cognitive interviewing, can produce actionable data that can add value to a study by enhancing and increasing the relevance of the knowledge generated. [24][25][26][27] Cognitive interviews help to assess and improve measurement tools and enhance understanding of the phenomenon being studied. 22,28 During a cognitive interview, after individuals are read each survey question, these individuals are probed regarding what they believe the question is asking and invited to describe information used to formulate a response.…”
Section: Methodsmentioning
confidence: 99%
“…Staphylococcus aureus and gram-negative bacterial bloodstream infections (SAB and GNB, respectively) are common and serious [ 1 , 2 ] infections that negatively impact survivors’ health-related quality of life (HRQoL), defined by and demonstrated across physical, functional, mental health/emotional, cognitive, and social domains [ 3 ]. Treatment of bloodstream infections often involves prolonged hospitalization, extended treatment and recovery times, and invasive procedures.…”
mentioning
confidence: 99%